Text mining e twitter : o poder das redes sociais num mercado competitivo - Veiga, Hugo Miguel Ferrão Casal da (2016)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence